3x-33=x+59

Simple and best practice solution for 3x-33=x+59 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-33=x+59 equation:


Simplifying
3x + -33 = x + 59

Reorder the terms:
-33 + 3x = x + 59

Reorder the terms:
-33 + 3x = 59 + x

Solving
-33 + 3x = 59 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-33 + 3x + -1x = 59 + x + -1x

Combine like terms: 3x + -1x = 2x
-33 + 2x = 59 + x + -1x

Combine like terms: x + -1x = 0
-33 + 2x = 59 + 0
-33 + 2x = 59

Add '33' to each side of the equation.
-33 + 33 + 2x = 59 + 33

Combine like terms: -33 + 33 = 0
0 + 2x = 59 + 33
2x = 59 + 33

Combine like terms: 59 + 33 = 92
2x = 92

Divide each side by '2'.
x = 46

Simplifying
x = 46

See similar equations:

| 6+-1+12=10x+7 | | h(t)=-4.9t+4t+3 | | 8w-5=6w+13 | | ln(3x-9)=y | | -10x-112=x+42 | | (6x+5)(x-2)=0 | | 3(2x-2)=-2(x+8)-12x | | k/4-19=6 | | X^2=-14x-13 | | (h*g)(x)=x^2*x+1 | | x+(x+9)*9=67 | | 6(N)=24 | | 2x+1=18x | | -4y-3=9 | | -75+9x=93+x | | x^4+16+36=15x^2-60 | | 4/9(n)=18 | | x*x*x-2118.74*x=8.5*8.5*8.5 | | 16=4-3v+6 | | (x*7.5)/52.5=y | | 4/9xn=18 | | 7-n=-9 | | 13+7w=55 | | 7y-5=3x+11 | | -1/9x=8 | | ×/.5=4.5 | | -6y+2(y-3)=-38 | | -27-x=-9x+30 | | 2x+(40x-1)*2=5 | | 6v+3(v+8)=15 | | 72-9=36 | | X+(2x+12)=54 |

Equations solver categories